Implementasi Reading Culture Dalam Menumbuhkan Minat Baca Siswa di SDIT X Depok - Rifina Dwiseptia Hanafi; Kiki Fauziah (Progam Studi Ilmu Perpustakaan UIN Sumatera Utara Medan, 2021)
This research discusses the implementation of Reading Culture in Developing Student’s Reading Interest in SDIT X di Depok. The goal of this research is to identify the implementation of Reading Culture in developing student’s reading interest with reading habituation. This research uses qualitative approach with case study method, and held from January 4th to June 14th 2020. The informants of this study were 7 (seven) students of sixth grade, the head of library, and the initiator of Reading Culture. The research of this study aims to show the implementation of Reading Culture in developing student’s reading interest. The findings in the implementation of Reading Culture are the rise of new culture and the Mobile Library considered as the most successful program. However, some programs were considered weak because of the hindraces from the students and teachers, the lack of socialization, and incondusive implementation. These implementations are expected to keep evaluated and developed to aims the goals to develops student’s reading interest.